Genome Size Variation and Comparative Genomics Reveal Intraspecific Diversity in Brassica rapa - Boutte, Julien; Maillet, Loeiz; Chaussepied, Thomas; Letort, Sébastien; Aury, Jean-Marc; Belser, Caroline; Boideau, Franz; Brunet, Anael; Coriton, Olivier; Deniot, Gwenaëlle; Falentin, Cyril; Huteau, Virginie; et al. (Frontiers in Plant Science, 2020)
Traditionally, reference genomes in crop species rely on the assembly of one accession, thus occulting most of intraspecific diversity. However, rearrangements, gene duplications and transposable element content may have a large impact on the genomic structure, which could generate new phenotypic traits. Using two Brassica rapa genomes recently sequenced and assembled using long-read technology and optical mapping, we investigated structural variants and repetitive content between the two accessions and genome size variation among a core collection. We explored the structural consequences of the presence of large repeated sequences in B. rapa ‘Z1’ genome versus the B. rapa ‘Chiifu’ genome, using comparative genomics and cytogenetic approaches. First, we showed that large genomic variants on chromosomes A05, A06, A09 and A10 are due to large insertions and inversions when comparing B. rapa ‘Z1’ and B. rapa ‘Chiifu’ at the origin of important length differences in some chromosomes. For instance, lengths of ‘Z1’ and ‘Chiifu’ A06 chromosomes were estimated in silico to be 55Mb and 29Mb, respectively. To validate these observations, we compared using fluorescent in-situ hybridization (FISH) the two A06 chromosomes present in a F1 hybrid produced by crossing these two varieties. We confirmed a length difference of 17.6% between the A06 chromosomes of ‘Z1’ compared to ‘Chiifu’. Alternatively, using a Copy Number Variation approach, we were able to quantify the presence of a higher number of rDNA and Gypsy elements in ‘Z1’ genome compared to ‘Chiifu’ on different chromosomes including A06. Using flow cytometry, the total genome size of 12 Brassica accessions corresponding to a B. rapa available core collection was estimated and revealed a genome size variation of up to 16% between these accessions as well as some shared inversions. This study revealed the contribution of long-read sequencing of new accessions belonging to different cultigroups of B. rapa and highlighted the potential impact of differential insertion of repeat elements and inversions of large genomic regions in genome size intraspecific variability.